Big data analysis of endovascular treatment for acute ischemic stroke: a study based on bibliometric analysis - Lu, Xin; Che, Huiying; Guan, Hongjian (Arquivos de Neuro-Psiquiatria, 2024)
Background While bibliometric analyses are prevalent in the medical field, few have focused on ther endovascular treatment for acute ischemic stroke (AIS).Objective To employ big data analysis to examine the research status, trends, and hotspots in endovascular treatment for AIS.Methods We conducted a comprehensive search using the Web of Science (WOS) database to identify relevant articles on the endovascular treatment for AIS from 1980 to the present. We used various tools for data analysis, including an online platform (https://bibliometric.com/app), the Citespace software, the Vosviewer software, and the ArcMap software, version 10.8. A number of bibliometric indicators were collected and analyzed, such as publication date, country where the studies were conducted, institutions to which the authors were affiliated, authors, high-frequency keywords, cooperative relationship etc.Results A total of 5,576 articles were retrieved. A substantial increase in the number of articles occurred after 2010. High-frequency keywords included terms such as large vessel occlusion, reperfusion, outcome, and basilar artery occlusion. Among the top 10 most productive authors, Raul G. Nogueira ranked first, with 136 published articles. Among the journals, The New England Journal of Medicine ranked first, with 5,631 citations. The United States has the closest collaborative ties with other nations.Conclusion In the present study, we found that the reports of endovascular treatment for AIS gradually increased after 2010. Among them, Raul G. Nogueira was the most productive author in this field. The New England Journal of Medicine was the most cited, and it had the greatest impact. The Multicenter Randomized Clinical Trial of Endovascular Treatment of Acute Ischemic Stroke in the Netherlands (MR CLEAN) trial study was the most cited, and it was a landmark study. There are many interesting studies on endovascular treatment for AIS, such as ischemic penumbra, collateral circulation, bridging therapy etc.
Keywords: Ischemic Stroke; Bibliometrics; Big Data